VARIATIONS OF LOW ENERGY NEUTRONS AND EARTHʹS SEISMOACTIVITY - Antonova, V.P.; Kryukov, S.V.; Lutsenko, V.Yu.; Malimbayev, A.M. (Academic Scientific Journal of Computer Science, 2020)
The results of the study of variations in the intensity of slow neutrons at the high-altitude Tien-Shan cosmic ray station (3340 m above sea level, 20 km from Almaty) are presented. The effect of cosmic and geophysical events on the flux of thermal and epithermal neutrons was successively analyzed. The comparison was made with well-known variations of high-energy neutrons of galactic origin recorded by the 18NM64 monitor. Like the 18NM64 neutron monitor, the installation for detecting thermal and epithermal neutrons is located near the Zailiysky fault of the earth’s crust. It has been established that, in the absence of seismic activity, the variations of thermal neutrons on the earth’s surface are of the same nature as the high-energy neutrons recorded by the monitor 18NM64. However, during the activation of seismic activity, the frequent breakdown of the correlation between the intensity of thermal and highenergy neutrons was noted. The cause of this phenomenon is the additional thermal neutron flux of the lithospheric origin, which appears under these conditions. It is shown that the amplitude of the additional thermal neutron flux from the Earth’s crust is equal to 5-7% of the background level. A difference was found also in the spectral composition of variations of slow and high-energy neutrons in the range (2·10-7 ÷ 2·10-6) Hz. Variations, due to the gravitational influence of the moon, are present throughout the 12-year period of research of thermal neutrons. The amplitude and its dynamics were determined. The analysis of our catalog of earthquakes in the vicinity of Almaty with an intensity of ≥ 3 points showed that 65÷70% of these events occurred during the full moon or new moon.